Analisa Faktor yang Berpengaruh terhadap Permintaan Tepung Terigu oleh Industri Kecil Berbahan Baku Tepung Terigu di Daerah Istimewa Yogyakarta - Saptati Nurul H.; Wahyu Supartono; Guntarti Tatik Mulyati (agriTECH, 2001)
This research was conducted to identify all influencing factors of wheat flour demand of industries, which used wheat flour as main raw material. Samples of this research were five noodle industries and ten sweet cake industries in Yogyakarta municipality. Dependent variable influencing to wheat flour demand of small scale industries were price of wheat flour, price of substitutes (rice flour and tapioca starch), industry's income, and governmental regulation for wheat flour distribution. A double regression method was used to determine the roles of each dependent variable. Result of data analysis showed, that the wheat flour demand was influenced by five factors in following equation: ... If the price of wheat flour (Pt) increased at 1%, the demand of it (Qt) decreased at 0.09%. The increase in price of rice flour (Ptb) 1% caused the increase in demand of wheat flour (Qt) for 0.124%; The increase in price of tapioca starch (Ptp) for 1% affected the increase in demand of wheat flour 0.028%; the increase of wheat flour demand of 0.427; also for cake industry increase in its income 1% caused increase in the wheat flour was stopped, the demand of wheat flour decreased. This regulation affected the declination of wheat flour demand in small-scale industry of wheat demand for 0.036.